Multiethnic democracy the logic of elections and policymaking in Kenya - Horowitz, Jeremy (New York Oxford University Press, 2022)
OXFORD STUDIES IN AFRICAN POLITICS AND INTERNATIONAL RELATIONS is a series for scholars and students working on African politics and International Relations and related disciplines. Volumes concentrate on contemporary developments in African political science, political economy, and International Relations, such as electoral politics, democratization, decentralization, gender and political representation, the political impact of natural resources, the dynamics and consequences of conflict, comparative political thought, and the nature of the continent's engagement with the East and West. Comparative and mixed methods work is particularly encouraged. Case studies are welcomed but should demonstrate the broader theoretical and empirical implications of the study and its wider relevance to contemporary debates. The focus of the series is on sub-Saharan Africa, although proposals that explain how the region engages with North Africa and other parts of the world are of interest
Includes bibliographical references (pages [171]-191) and index.
Keywords: Elections--Kenya.